Índices bióticos mono e multimétricos de avaliação da qualidade da água em riachos da Mata Atlântica - Yoshida, Claudia Eiko; Uieda, Virginia Sanches [UNESP] (My University, 2013)
Protocols for rapid habitat evaluation and the biotic indices used in biomonitoring of streams in Brazil provide useful information about water quality and modifications in the ecosystem. However, the interpretation of their results is limited. Previous studies pointed out the low sensitivity of those indices to measure the quality of low-order streams, since they only measure organic impacts. Environmental degradation of these streams is mainly related to impacts caused by landscape change, such as erosion, siltation, channel change, loss of riparian vegetation, and reduction in water flow. The streams of the Serra do Japi are under some of these impacts, caused by agricultural activities. In this study, we evaluated whether the reduction of natural characteristics in these environments would decrease water quality. The Protocol of Habitat Diversity was affected by the impacts of agricultural activities. However, the other three biotic indices: Biological Monitoring Working Party Score System, Average Score Per Taxon, and Index of Benthic Community were not as sensitive to those impacts, since they all indicated a high water quality. An adaptation of the attributes and the scoring system is suggested for defining better policies for the conservation of this area.

Os protocolos de avaliação de hábitats e os índices bióticos utilizados no biomonitoramento de rios no Brasil fornecem boas informações sobre a qualidade da água e indicações sobre as modificações do ecossistema aquático. No entanto, a interpretação de seus resultados têm limitações. Estudos anteriores apontaram limitações destes índices para aferir a qualidade de riachos de baixa ordem, já que os índices medem somente impactos orgânicos. A degradação ambiental desses riachos está relacionada principalmente a impactos causados pela alteração da paisagem, tais como erosão, assoreamento, retificação do canal, perda de mata ciliar, e redução do fluxo da água. Os riachos da Serra do Japi estão sujeitos a alguns desses impactos provocados por atividades rurais. Portanto, neste estudo foi avaliado se a redução das características naturais de alguns desses ambientes diminuiria a qualidade da água. A pontuação obtida pela aplicação do Protocolo de Diversidade de Hábitat salientou a ação de impactos difusos da atividade agrorrural sobre a qualidade do hábitat. Porém, os índices bióticos aplicados - Biological Monitoring Working Party Score System, Average Score Per Taxon e Índice da Comunidade Bentônica para Rios -, não foram afetados pelos usos do entorno dos riachos, já que apontaram alta qualidade da água de todos os ambientes analisados. Uma adequação dos atributos e da classificação a partir das pontuações é sugerida para uma melhor definição de políticas de conservação da área.
Keywords: Cabreúva; Hábitat diversity; Jundiaí; Macroinvertebrates; Headwaters; Cabreúva; Diversidade de hábitat; Jundiaí; Macroinvertebrados; Nascentes